Acute effects of sauna bathing on cardiovascular function. (February 2018) - Laukkanen, Tanjaniina; Kunutsor, Setor; Zaccardi, Francesco; Lee, Earric; Willeit, Peter; Khan, Hassan; Laukkanen, Jari
Abstract Emerging evidence suggests beneficial effects of sauna bathing on the cardiovascular system. However, the effects of sauna bathing on parameters of cardiovascular function and blood-based biomarkers are uncertain. We aimed to investigate whether sauna bathing induces changes in arterial stiffness, blood pressure (BP), and several blood-based biomarkers. We conducted an experimental study including 102 participants (mean age (SD): 51.9 (9.2) years, 56% male) who had at least one cardiovascular risk factor. Participants were exposed to a single sauna session (duration: 30 min; temperature: 73 °C; humidity: 10–20%). Cardiovascular as well as blood-based parameters were collected before, immediately after, and after 30-min recovery. Mean carotid–femoral pulse wave velocity was 9.8 (2.4) m/s before sauna and decreased to 8.6 (1.6) m/s immediately after sauna (p < 0.0001). Mean systolic BP decreased after sauna exposure from 137 (16) to 130 (14) mmHg (p < 0.0001) and diastolic BP from 82 (10) to 75 (9) mmHg (p < 0.0001). Systolic BP after 30 min recovery remained lower compared to pre-sauna levels. There were significant changes in hematological variables during sauna bathing. Plasma creatinine levels increased slightly from sauna until recovery period, whereas sodium and potassium levels remained constant. This study demonstrates that sauna bathing for 30 min has beneficial effects on arterial stiffness, BP, and some blood-based biomarkers. These findings may provide new insights underlying the emerging associations between sauna bathing and reduced risk of cardiovascular outcomes.